Wave propagation in a steady supersonic flow of a radiating gas past plane and axisymmetric bodies - Singh L.P.; Sharma V.D.; Gupta N. (My University, 2025)
Using the method of wavefront analysis the paper presents an analysis of shock wave formation in a two-dimensional steady supersonic flow of a radiating gas past plane and axisymmetric bodies such as a beak and sharp edged ring. Transport equations are derived which lead to the determination of the shock formation distance and also to conditions which insure that no shock will ever evolve on the wavefront. It is assessed as to how the shock formation distance is influenced by the presence of thermal radiation, the initial body curvature and upstream flow Mach number M0>1. © 1988 Springer-Verlag.